Forensically important insects associated with the decomposition of mice carrion in Bangladesh - Islam, Maidul; Hossain, Asma; Mostafa, Md Golam; Hossain, Md Monwar (Jahangirnagar University Journal of Biological Sciences, 2016)
Investigations on the incidence, abundance and succession of some forensically important insects associated with mammalian carrion and their role in the decomposition of the carrion were carried out in Jahangirnagar University campus, Savar, Bangladesh. A total of twelve insect species under ten insect families belonging three orders were collected and identified during this study. The ten families viz Calliphoridae, Muscidae, Piophilidae, Sarcophagidae under the order of Diptera, the family Formicidae under the order of Hymenoptera and Silphidae, Cleridae, Histeridae and Dermestidae under the order of Coleoptera were found in mice carrion. The most abundant insects were Formicidae (55.5%) followed by Muscidae (21. 21%) and Calliphoridae (10.3%). They appeared at the first stage but Dermestidae was recorded at the last stage of decomposition of the carcass. This study on mice/mammalian system could be followed by researchers and might contribute to the medico-legal purposes as well as could impart knowledge to develop a biomonitoring model in Bangladesh. Jahangirnagar University J. Biol. Sci. 5(1): 11-20, 2016 (June)